Exploring regional variations in the cross‐cultural, international implementation of the Patient Reported Outcomes Burdens and Experience (PROBE) study. Issue 3 (12th March 2019) - Chai‐Adisaksopha, Chatree; Skinner, Mark W.; Curtis, Randall; Frick, Neil; Nichol, Michael B.; Noone, Declan; O'Mahony, Brian; Page, David; Stonebraker, Jeffrey; Thabane, Lehana; Crowther, Mark A.; Iorio, Alfonso
Abstract: Background: The Patient Reported Outcomes Burdens and Experience (PROBE) study has developed and validated the PROBE questionnaire for assessing patient‐reported outcomes in people with haemophilia and participants without bleeding disorders. Objective: To explore the regional variations in the international implementation of the PROBE questionnaire. Methods: Data were collected from participants in four regions (Western Pacific, South America, North America and Europe). Participants were able to choose English or translated versions of the PROBE questionnaire into their first language. We used analysis of variance methods and multivariable regression to determine the relative contribution of the variance explained by region controlling for haemophilia diagnosis, age group and levels of educations. We also explored interactions between region and the other components. Results: We used 862 questionnaires from 14 countries. Mean age of participants was 40.03 years (standard deviation 13.89), and 73.67% were male. After adjusting, region contributed 0.44%‐7.98% of the variance component in subitem scores and 0.26% in the PROBE score. Years of education contributed 0.34% in the PROBE score. Age and haemophilia diagnosis contributed 3.42% and 22.42% of the PROBE score. Conclusions: The results demonstrate that the PROBE questionnaire is valid to implement for assessing health status among patients with haemophilia and participants without bleeding disorders across regions.